Economic science and economic-mathematical modeling - Veduta, E.N.; Dzhakubova, T.N. (Математичне моделювання в економіці, 2017)
The global crisis, which has required a rethinking of economic knowledge and corresponding economic and mathematical models (EMM), makes us to return to the origins of the economic science and EMM. Thus the exceptional urgency to exit the global crisis gains the Marx theory of reproduction which study the objective economic laws, and the EMM based on this theory which helps to build the cyber system in order to enter the path of the social progress. The article shows that the EMM, which historical goal was to understand the economic mechanisms deeper, has been developed in two main directions. The article sets out the basic principles of the dynamic model of inter-branch and inter-sectoral balance (MIIB), which can be the basis for the creation of economic cyber system.